Potential Applications of Antifragility Principles in the Logistic - Pawellek, Patrick (Digital Repository of Theses, 2026)
The logistics industry plays a central role in the global economy by enabling the cross-border movement of goods and services. The COVID-19 pandemic and other geopolitical conflicts or unpredictable events in supply chains have highlighted the vulnerability of the logistics industry. They have shown that global supply chains are far more susceptible to crises or disruptions than previously assumed. This vulnerability can lead to unpredictable chain reactions, which in turn have a significant impact on the global economy and the companies, institutions and economies within it. Based on Taleb's concept of "antifragility" from his 2013 book, this paper explores the paradigm shift from mere resilience to shocks (robustness) to profiting from unpredictable events and crises. Despite the potential to revolutionize organizational preparedness and response to crises, the application of antifragility in the logistics industry has not yet been sufficiently researched and utilized. This dissertation seeks to address this gap by mapping the industry's current resilience practices, identifying potential applications for antifragility, examining concrete strategies for applying antifragility, and proposing a comprehensive framework for integrating antifragility strategies in the logistics sector. The research aims to give companies in the logistics sector the opportunity to become antifragile through concrete applications that they can implement in their business apparatus and thus profit from unforeseeable events and crises.